Evaluation of the quality of life before and after functional endoscopic sinus surgery among patients with nasal polyps by means of SF-36 questionnaire - Deeba, Farah; Abbas, Syed Waseem; Ali, Ihsan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aim of the study was to evaluate the quality of life before and after FESS among patients with nasal polyps. Material and Method: This study was done in Government Medical College Srinagar from January 2019 to December 2019 for a period of 12 months. A total of 69 patients with nasal polyposis who underwent FESS were included in the study. They were given a questionnaire SF-36 to be fulfilled preoperatively, 3 months and at 6 months after surgery. Result: The preoperative SF-36 score was 79.35 and postoperative score was 83.62 at 3 months, 86.88 at 6 months. Conclusion: SF-36 questionnaire values showed improvement at 3 months and then at 6 months of follow up.